Properties of N-rich Silicon Nitride Film Deposited by Plasma-Enhanced Atomic Layer Deposition. (July 2017) - Jhang, Pei-Ci; Lu, Chi-Pin; Shieh, Jung-Yu; Yang, Ling-Wu; Yang, Tahone; Chen, Kuang-Chao; Lu, Chih-Yuan
Highlights: N-rich silicon nitride film with a wide range N/Si ratio by PEALD process. Study the kinetics of the PEALD process for N-rich silicon nitride films. The application of N-rich silicon nitride films as charge-trapping layer in MAONOS devices. Abstract: An N-rich silicon nitride film, with a lower refractive index (RI) than the stoichiometric silicon nitride (RI = 2.01), was deposited by alternating the exposure of dichlorosilane (DCS, SiH2 Cl2 ) and that of ammonia (NH3 ) in a plasma-enhanced atomic layer deposition (PEALD) process. In this process, the plasma ammonia was easily decomposed to reactive radicals by RF power activating so that the N-rich silicon nitride was easily formed by excited ammonia radicals. The growth kinetics of N-rich silicon nitride were examined at various deposition temperatures ranging from 400 °C to 630 °C; the activation energy (Ea ) decreased as the deposition temperature decreased below 550 °C. N-rich silicon nitride film with a wide range of values of refractive index (RI) (RI = 1.86–2.00) was obtained by regulating the deposition temperature. At the optimal deposition temperature, the effects of RF power, NH3 flow rate and NH3 flow time were on the characteristics of the N-rich silicon nitride film were evaluated. The results thus reveal that the properties of the N-rich silicon nitride film that was formed by under plasma-enhanced atomic layer deposition (PEALD) are dominated by deposition temperature. In charge trap flash (CTF) study, an N-rich silicon nitride film was applied to MAONOS device as a charge-trapping layer. The films exhibit excellent electron trapping ability and favor a fresh cell data retention performance as the deposition temperature decreased.